Diffusion Affine Projection Sign Algorithm based on QR-Decomposition - Sitjongsataporn, Suchada; Prongnuch, Sethakarn; Wiangtong, Theerayod (My University, 2021)
In this paper, an Adapt-Then-Combine diffusion strategy on affine projection sign algorithm is presented. Based on the QR-decomposition method, the modified inverse autocorrelation matrix is shortly brief to decrease the computational complexity. The Adapt-Then-Combine diffusion strategy is applied on the low complexity of sign algorithm version of inverse square-root affine projection algorithm including with the adaptation and combination steps. By applying an idea of diffusion adaptation algorithm, we derive a diffused version of an affine projection sign algorithm based on QR-Decomposition, denoted as DiQR-APSA. Experimental results show that the proposed DiQR-APSA can achieve the good performance in comparison with the standard affine projection sign algorithm.
Keywords: Affine projection algorithm; Diffusion strategy; QR-Decomposition; Sign algorithm